Poly (2-hydroxyethyl methacrylate) particles for management of hemorrhage of complicated origin: treatment of hemobilia - Horák, D; Guseinov, E; Adamyan, A; Titova, M; Danilov, M; Trostenyuk, N; Voronkova, O; Gumargalieva, K (Journal of biomedical materials research, 1996)
Poly (2-hydroxyethyl methacrylate) (PHEMA) particles of cylindrical and spherical shape were developed as a preparation for tumor treatment or control of hemorrhage by blocking their blood supply. In this report, PHEMA particles were used for the management of hemobilia, that is, bleeding into biliary passages. The origin of hemobilia in 31 patients was localized by selective angiography. With the objective of prophylaxy of hemorrhage, selective embolization with PHEMA particles of the branches of the hepatic artery responsible for the supply of blood to the focus of damage was used in 18 patients. This low-trauma method allowed either a complete control of bleeding or, at least, intraoperative blood loss was reduced more than twice. Histological investigation of the occluded blood vessels showed that the thrombus was attached to the particles and was reinforced by the porous structure of the polymer. A hypercoagulation reaction was observed in the postembolization period. This allowed correction of the hypocoagulation in the hemostasis system.
Keywords: Embolization, Therapeutic; hemobilie; Liver; Blood Loss, Surgical; játra; Hemobilia; Middle Aged; mužské pohlaví; žlučové cesty intrahepatální; krvácení při operaci; Humans; Bile Ducts, Intrahepatic; Microspheres; biologické markery; patologická angiogeneze; Polyhydroxyethyl Methacrylate; lidé středního věku; Neovascularization, Pathologic; Blood Coagulation; polyhydroxyethylmethakrylát; Biomarkers; terapeutická embolizace; mikrosféry; hemokoagulace; lidé; Male